Assessment and Prediction of Coastal Ecological Resilience Based on the Pressure–State–Response (PSR) Model - Zhaoyi Wan; Chengyi Zhao; Jianting Zhu; Xiaofei Ma; Jiangzi Chen; Junhao Wang (Land)
Coastal zones are facing intensive ecological pressures and challenges, which could vary over a wide range of spatiotemporal scales. Our limited capability to understand and especially predict this variability can lead to the misinterpretation of coastal ecological resilience. Therefore, the assessment and prediction of ecological resilience are particularly important. In this study, a new approach based on the Pressure–State–Response model is developed to assess and predict pixel-scale multi-year ecological resilience (ER) and then applied to investigate the spatiotemporal variations of ER in the China’s coastal zone (CCZ) in the past few decades and predict future ER trend under various scenarios. The results show that ER in the CCZ displayed a general spatial distribution pattern of “higher in the southern half and lower in the northern half” from 1995 to 2020. Over the 25-year period, ER exhibited a declining trend. Specifically, the eastern provinces experiencing the most significant decline. The ER levels across scenarios ranked from high to low as follows: SSP1-2.6 > SSP4-3.4 > SSP2-4.5 > SSP3-7.0 > SSP5-8.5. The assessment and prediction methods designed can be applied to ER studies in other coastal zones, making it a valuable approach for broader applications.